Geographic Distribution of Providers With a DEA Waiver to Prescribe Buprenorphine for the Treatment of Opioid Use Disorder: A 5‐Year Update. Issue 1 (20th June 2018) - Andrilla, C. Holly A.; Moore, Tessa E.; Patterson, Davis G.; Larson, Eric H.
Abstract: Purpose: Opioid use disorder (OUD) is a substantial public health problem. Buprenorphine is an effective medication‐assisted treatment (MAT) for OUD, but access is difficult for patients, especially in rural locations. To improve access, the Comprehensive Addiction and Recovery Act of 2016 extended the ability to get a Drug Enforcement Administration (DEA) waiver to prescribe buprenorphine to treat OUD to nurse practitioners (NPs) and physician assistants (PAs). This study summarizes the geographic distribution of waivered physicians, NPs, and PAs at the end of 2017 and compares it to the distribution of waivered physicians 5 years earlier. Methods: Using the DEA list of providers with a waiver to prescribe buprenorphine to treat OUD and the Area Health Resources File, we assigned waivered providers to counties in 1 of 4 geographic categories. We calculated the number of counties in each category that did not have a waivered provider and county provider to population ratios and then compared our results to the waivered workforce in 2012. Findings: The availability of a physician with a DEA waiver to provide office‐based MAT has increased across all geographic categories since 2012. More than half of all rural counties (56.3%) still lack a provider, down from 67.1% in 2012. Almost one‐third (29.8%) of rural Americans compared to 2.2% of urban Americans live in a county without a buprenorphine provider. NPs and PAs add otherwise lacking treatment availability in 56 counties (43 rural). Conclusions: Overall, MAT access has improved, but rural communities still experience treatment disparities.